Use of dermápteros in the agronomic scenario: a bibliometric analysis on the use of these predators (Research, Society and Development, 2021)
The objective of this study was to make an inventory of the scientific works published in the last 10 years on the use of dermopterans in the agronomic scenario. To this end, a literature review was carried out, looking for published scientific research on the use of dermapters in the agronomic scenario. The search for this information occurred between the months of December 2020 and February 2021 in the databases: Web of science, ScienceDirect, Taylor & Francis, Springer, Scielo, using as keywords “Dermaptera”, “Predators”. The inclusion criteria for studies in the review were language (articles in English, Portuguese and Spanish), research articles, date of publication (published in the last 10 years) and relationship with the subject studied. After the selection based on the aforementioned criteria, the selected studies were read in full and the data collected were organized in a spreadsheet using Microsoft Excel. Based on the eligibility criteria, a total of 1,626 studies were found, of which 466 were selected for complete reading, after reading, only 65 articles corresponded to the topic. From these it was possible to obtain information such as: studied dermopteran species, study areas, geographic distribution, years of publication, area of application and species of predated pests. The survey highlights the scarcity of research on the subject. However, the high amount of studies about the species Forficula auricularia stands out. The research in question, points to Brazil as the country that most published on the subject, and reveals that the focus of the studies made reference to the use of these insects in the biological control of agricultural pests.